Dinamika Tantangan dan Peluang dalam Implementasi MPAI di SD pada Era Kontemporer - Taufik Hidayat; Moh Affan Annabily; Muhammad Syafiq Rahman Zain (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
Islamic Religious Education (MPAI) at the elementary school level has a very important role in shaping the character and morality of students. However, in the midst of technological development, globalization, and rapid social change, MPAI faces various challenges. One of the main challenges is the low understanding of the community and students regarding the importance of religious education. In addition, diverse perspectives on religious teachings and moral values contribute to the difficulty in designing appropriate teaching materials for students. The influence of digital technology also poses its own challenges, where students are more exposed to information that sometimes contradicts the religious values taught in schools. However, the contemporary era also provides great opportunities for the development of MPAI learning. The utilization of digital technology, such as educational applications, social media, and online learning platforms, allows for a more engaging and interactive presentation of teaching materials. With technology, religious learning becomes more flexible, effective and efficient, and can reach a wider range of students. In addition, the integration of religious values with contemporary issues in teaching materials can increase the relevance of religious education among students. Therefore, educators need to develop innovative methods, utilize technology wisely, and strengthen students' understanding of religious values in daily life. This article aims to identify the challenges faced by MPAI in primary schools in the contemporary era, while exploring the opportunities that exist to optimize religious learning. The author also provides recommendations to improve the quality of religious education in the midst of changing times.